Buddhist Pilgrimage in Bihar India: A Tourism Policy Perspective - Upadhya, Amitabh (The international journal of religious tourism and pilgrimage, 2020)
ourism policies formulated and implemented by the union and state governments of India and Bihar respectively, over the past five decades, have played a significant role in attracting religious tourists to the Buddhist sites in Bihar from all across the world. This exploratory research is a historiographical narrative of Buddhist tourism in view of tourism development policies and plans. The study finds that favourable and effective policies have increased domestic and foreign tourism in India, especially international Buddhist pilgrimage to Bihar. However, the state of Bihar still needs better policies and marketing to promote Buddhist tourism. The paper explores the overlooked role of government tourism development policies in promoting spiritual and religious tourism in India, in addition to chronicling the development of tourism in Bihar. The study paves the path for further research into a potential tourism resource that the state of Bihar possesses but has not been able to fully realise. This case study is one of very few attempts to relate the role of policies in the development of tourism in South Asia